Adverse skin reactions to antiepileptic drugs - a review - Gruszczyńska, Michalina; Jarzemski, Adam; Kolossa, Agnieszka; Porzych, Rafał (Journal of Education, Health and Sport, 2023)
Introduction and objective: Treatment with antiepileptic drugs (AEDs) is frequently used all around the world. Just like in the course of all the drugs administration, side effects may appear, including characteristic side effects presenting on the skin. The aim of the study was to analyse adverse skin reactions to antiepileptic drugs, focusing on their epidemiology, symptoms and treatment. Methods: Databases including PubMed and Google Scholar were browsed using keywords. Description of the state of knowledge: The majority of adverse skin reactions (ASRs) constitute mild rashes and urticaria, however in about 10% cases severe reactions may occur, which can be life-threatening. They include Drug Reaction with Eosinophilia and Systemic Symptoms (DRESS), Stevens-Johnson syndrome (SJS), Toxic Epidermal Necrolysis (TEN), Serum Sickness and Serum Sickness - like Reactions and Drug Induced Vasculitis. In the course of TEN mortality rates are highest, however all reactions can be dangerous and treatment should be applied immediately. In mild and moderate cases drug withdrawal is usually sufficient, however more severe cases need to be treated with immunosuppressive agents. Summary: The awareness about possible adverse effects and their treatment is crucial as some can be life-threatening and immediate therapy increases the chance of recovery.